Evaluation of the Antimicrobial Activity and Toxicity of Local and Foreign Seeds of Azanza Garckeana (Goron Tula) Extracts - Abdullahi Isiaka Hassan; Aishatu Ibrahim Aminu (UMYU Journal of Microbiology Research)
Drug resistance poses a challenge to antimicrobial treatment options necessitating the continuous search of plant extracts with therapeutic potentials. The study determines the antimicrobial activities and toxicity effect of local and foreign seeds of Azanza garckeana. Constituents of the seeds of A. garckeana were extracted and identified using standard phytochemical procedures. Clinical isolates from patients diagnosed with Urinary Tract Infections (UTIs) were confirmed using standard microbiological procedures. Disk diffusion techniques were used to assess the antimicrobial properties of the plant extract, and Mass Spectrometry and Gas Chromatography were used to identify the bioactive components. Toxicity of plant extract was assessed using acute toxicity test, histopathological and hematological studies. The findings indicated the existence of alkaloids, carbohydrates, saponins, tannins and flavonoids in both local and foreign seeds of A. garckeana. Five (5) organisms were identified from patient with UTIs. Antimicrobial activities showed that the Petroleum ether extract of foreign A. garckeana exhibited higher antibacterial activity against Staphylococcus aureus (15mm), Pseudomonas aeruginosa (13mm) than Petroleum ether extract of local A. garckeana at a concentration of 200µg/ml respectively. Similarly, A. garckeana foreign aqueous extracts showed higher activity against S. aureus (13mm), and P. aeruginosa (12mm) than local Aqueous A. garckeana at a concentration of 200µg/ml respectively. The GCMS analysis showed the existence of Dodecanoic acid, ethyl ester, Octadecenoic acid, Undecanoic acid and methyl ether. Both the local and foreign seeds of A. garckeana were found to be non-toxic at ≤ 600 mg/kg. Histopathological and hematological studies showed heart with normal features, kidney with slight hyperplasia of inflammatory cells and liver with slight hepatic necrosis at 1000 mg/kg. The study demonstrated that the local and foreign seeds of Azanza garckeana had antimicrobial therapeutic potential but its usage should be dose dependent not exceeding ≤ 600 mg/kg.